Calculating correct compilers II: Return of the register machines. (20th August 2020) - BAHR, PATRICK; HUTTON, GRAHAM
Abstract: In 'Calculating Correct Compilers' (Bahr & Hutton, 2015 ), we developed a new approach to calculating compilers directly from specifications of their correctness. Our approach only required elementary reasoning techniques and has been used to calculate compilers for a wide range of language features and their combination. However, the methodology was focused on stack-based target machines, whereas real compilers often target register-based machines. In this article, we show how our approach can naturally be adapted to calculate compilers for register machines.